Deformations at the craniofacial complex depending on the HYRAX device design - Sergei Bosiakov; Anastasiya Vinakurava; Andrei Dosta (Advances in Mechanical and Materials Engineering, 2015)
Finite element analysis of the stress-strain state of a human skull after the expansion of the maxilla with using different designs orthodontic appliance HYRAX was carried out. Finite element model of craniofacial complex and supporting teeth are obtained on the basis of tomographic data. An orthodontic appliance differs by the localization of the screw relative to the palate. The design with location of the rods and screw of device in the same horizontal plane as well as the design with the location of the screw at the 8 mm closer to the palate relative to the horizontal localization are considered. Deformations at the intact skull and a skull with a cleft palate were derived. The regions of the largest deformations of the skull bone structures are defined for different orthodontic device designs. Effect of the orthodontic device design on displacements of the supporting teeth is analyzed. The results can be used to design devices HYRAX for the orthodontic correction and treatment of the cross-bite patients.